Association between triglyceride to HDL‐C ratio and insulin resistance in indigenous Argentinean children. Issue 8 (10th October 2014) - Hirschler, V.; Maccallini, G.; Sanchez, M.; Gonzalez, C.; Molinari, C.
Abstract : Background: Insulin resistance is considered one of the major risk factors for the development of type 2 diabetes mellitus (T2DM). Thus, early identification, preferably by using simple and inexpensive diagnostic tools, is essential for preventing T2DM. Triglyceride (TG) to high‐density lipoprotein cholesterol (HDL‐C) ratio (TG/HDL‐C) has been proposed as an inexpensive tool to identify individuals at high risk of T2DM. The objective of this study was to determine the relationship between insulin resistance and TG/HDL‐C in indigenous Argentinean children. Methods: A cross‐sectional study of 501 (243 boys) indigenous school children aged 10.0 ± 2.4 yr were assessed for anthropometry, lipids, glucose, and insulin levels from November 2011 to November 2013. Insulin resistance was defined as the upper third quartile of homeostasis model assessment (HOMA‐IR). Results: The prevalence of overweight/obesity was 11.4% per Centers for Disease Control. Mean levels of various characteristics were: body mass index (BMI) 17.2 ± 2.6, HDL‐C 39 ± 9 mg/dL, TGs 121 ± 58 mg/dL, TG/HDL‐C 2.9 ± 1.8, glucose 77 ± 8 mg/dL, HOMA‐IR 1.0 ± 0.8, and insulin 44 ± 9 mUI/L. Children in the higher quartiles of TG/HDL‐C had significantly higher HOMA‐IR values than children in the lower quartiles. Multiple linear regression analysis showed that TG/HDL‐C was significantly associated with HOMA‐IR (r 2 = 0.19) adjusted for age, gender, and BMI. Furthermore, for a 1‐unit increase in log TG/HDL‐C, the odds of being insulin resistant (HOMA‐IR>III quartile) increased by 2.58 times [odds ratio (OR), 2.58 (1.63–4.05); p < 0.01], adjusted for age, gender, and BMI. Conclusion: This study suggests that TG/HDL‐C may be a good marker to identify insulin resistant indigenous Argentinean children.